Analytical Study of Brahmi Ghrtia: A Polyherbal Ayurvedic Compound (International Journal of Ayurveda and Pharma Research, 2025)
Brahmi Ghrita was processed as per the process of Snehapaka procedure described in classics. It contained Brahmi (Bacopa monneri), Sunthi (Zingiber officinale), Maricha (Piper nigrum), Pippali (Piper longum), Shyama (Operculina turpethum), Trivrit (Operculina turpethum), Danti (Baliospermum montanum), Sankhpuspi (Convolvulus pluricaulis), Nrpadruma (Cassia fistula), Saptala (Euphorbia dracunculoides), and Vidanga (Embelia ribes), were mixed in Ghrita and heated for three hours at 110°C every day for three days. On the third day Ghrita was filtered to obtain the finished product. In this manner, three samples of Brahmi Ghrita were prepared. To understand the changes that occurred during the preparation, Brahmi Ghrita were analysed by using modern parameters such as acid value, saponification value, and so on. After the analysis, it was found that the Rancidity were absent in Brahmi Ghrita; acid values of Brahmi Ghrita were 1.81; the saponification values were 212.30; the iodine values were 39.17; the refractive index was 1.4590; the moisture were 0.12%; and the specific gravity were 0.9441 respectively. The present study revealed that, there was no significant variation in the analytical values among all three samples of Brahmi Ghrita. TLC was carried out after organizing appropriate solvent system in which maximum 6 spots were distinguished.